Enhancing Employee Performance: A Leadership Analysis - Basalamah, Indira; Carda P, Muhammad; A. Bahasoan, Nizmah (Journal of Management, 2024)
This study seeks to offer an overview and analysis of the function of leadership at PT. Bogatama Marinusa. This study's research technique is qualitative, utilizing a descriptive approach. Primary data was gathered via interviews with eight firm workers who served as research informants. The study's findings show that leadership plays an important role in improving employee performance at PT. Bogatama Marinusa, with the leader performing interpersonal roles such as the figurehead role, which represents the company, the leader role, which provides motivation, and the liaison role, which maintains communication with employees. The information role comprises of the monitoring function, which is obtaining information from different sources; the disseminator's duty is to constantly update the most recent information; and the spokesperson's role is to transmit information to third parties. Decision making comprises of the entrepreneurial function, which is to provide ideas for employment renewal, the role of managing disruptions as a dispute mediator, the role of distributing resources by channeling money openly, and the role of negotiator by engaging in talks. The study findings indicate that the leadership position has a major impact on staff performance